Understanding the religions of the world: an introduction - Deming, Will (John Wiley & Sons Ltd, 2025)
"World Religions is one of the most widely offered courses on the Religion and Theology curriculum to introduce students to the study of religion. Despite the competitive market, Understanding the Religions of the WorldÂ is praised by adopters as a comprehensive and rigorous textbook ideal for undergraduate students. With 4,000+ copies sold over six years, this title is valued for its combination of historical context, contemporary beliefs and practices, and original theory, with numerous study features and valuable overviews. Building on the success of the first edition (published in 2015), volume editor Will Deming aims to fully revise and update the content to focus on religious traditions that play a part in current world affairs. This will expand the target audience of the book, allowing cross-reference between other disciplines within social sciences"--